AHR canonical pathway: in vivo findings to support novel antihypertensive strategies. (March 2021) - Coelho, Nuno R.; Matos, Clara; Pimpão, António B.; Correia, M. João; Sequeira, Catarina O.; Morello, Judit; Pereira, Sofia A.; Monteiro, Emília C.
Graphical abstract: Highlights: Consistent in vivo data exists on the association between the canonical pathway of the aryl hydrocarbon receptor (AHR) and hypertension (HTN). There is strong evidence on the association between exogenous AHR ligands and HTN. Further developments are needed on the mechanisms interlinking ligands-AHR-HTN. The profile of AHR ligands that characterize the AHR-related phenotype of HTN needs to be disclosed. A better understanding is needed on the relation of CYP1A1 activity and HTN. Abstract: Essential hypertension (HTN) is a disease where genetic and environmental factors interact to produce a high prevalent set of almost indistinguishable phenotypes. The weak definition of what is under the umbrella of HTN is a consequence of the lack of knowledge on the players involved in environment-gene interaction and their impact on blood pressure (BP) and mechanisms. The disclosure of these mechanisms that sense and (mal)adapt to toxic-environmental stimuli might at least determine some phenotypes of essential HTN and will have important therapeutic implications. In the present manuscript, we looked closer to the environmental sensor aryl hydrocarbon receptor (AHR), a ligand-activated transcription factor involved in cardiovascular physiology, but better known by its involvement in biotransformation of xenobiotics through its canonical pathway. This review aims to disclose the contribution of the AHR-canonical pathway to HTN. For better mirror the complexity of the mechanisms involved in BP regulation, we privileged evidence from in vivo studies. Here we ascertained the level of available evidence and a comprehensive characterization of the AHR-related phenotype of HTN. We reviewed clinical and rodent studies on AHR-HTN genetic association and on AHR ligands and their impact on BP. We concluded that AHR is a druggable mechanistic linker of environmental exposure to HTN. We conclude that is worth to investigate the canonical pathway of AHR and the expression/polymorphisms of its related genes and/or other biomarkers ( e.g. tryptophan-related ligands), in order to identify patients that may benefit from an AHR-centered antihypertensive treatment.